Eksistensi Perkampungan Setu Babakan Sebagai Daya tarik Wisata Budaya Betawi, Jakarta Selatan - Pehulisya, Ricky Leonardo; Nugroho, Saptono (JURNAL DESTINASI PARIWISATA, 2020)
Babakan Lake is an icon of the Betawi village which was inaugurated by the DKI Jakarta government as a cultural tourist attraction in Jakarta. Betawi arts and culture are increasingly lost by the progress of time. Therefore, the importance of this research is to look at how community participation around villages in promoting Betawi culture in the context of 4A (amenities, accessibility, attractions, institutions). Data collection techniques used in this study were unstructured interviews, observation and documentation. Determination of informants using purposive sampling, data analysis using qualitative. The implementation of tourism activities in Betawi village in the form of facilities, accessibility and institution has fulfilled the criteria as a tourist attraction. Like the Lake Babakan attraction as an icon of the Betawi village. Then also the facilities provided by the government to preserve and advance Betawi villages such as zones that are divided into areas and are motivated by different concepts of each zone. Furthermore, access to the tourist attraction of Lake Babakan has fulfilled the assessment and determination as a tourist area both from the road and the direction of the guide to the location of government and citizens institutions formed by local customary stakeholders. The result of the participation of citizens in tourism activities towards the existence of the Betawi village is that citizens have a role in advancing Betawi art. Suggestions for tourism stakeholders such as government, private sector and citizens in advancing, developing and also preserving the Betawi village is to maintain the existence of the village in the midst of the current development. Such as promoting the existence of a Betawi village to Jakarta residents (millennial, companies, foreign representatives in Jakarta). Keywords: Betawi Cultural Village, Tourism Practices, Existence